Frontiers in New Drug Discovery: From Molecular Targets to Preclinical Trials (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The intention of this Special Issue is to focus on new aspects of drug discovery, including the search for new molecular targets of various diseases, the creation of new modern methods for diagnosing diseases, the development of new test systems and kits for assessing the selectivity and effectiveness of new drugs, the study of the molecular mechanisms of biologically active compounds, the formulation of new drugs, pharmacokinetic and pharmacodynamic studies, and preclinical trials of important molecules.